Nowa filozofia mediów w Niemczech - Hudzik, Jan P. (Humaniora. Czasopismo Internetowe, 2020)
This article is about the philosophy of media developed in Germany as early as at the end of the 20th century. It was appeared as the Medienphilosophie – media philosophy – due to a coincidence of two different events that happened in social theory and practice – it’s when the end of certain period in German philosophy coincided then with the beginning of cyber civilization. The understanding of the latter situation demands the creation of a new language – a new analytical and critical apparatus capable of grasping reality becoming more and more medialized. The problem is not so much a question of particular media, but mediality itself. The reconstruction of the philosophy in question does not consist of the presentation of the views expressed by all its authors. It is less about substantive findings of this philosophy and more about its meta-theoretical aspects – the ontological and epistemological assumptions, conceptual apparatus, modes of justification. This text consists of five parts. The first two ones present origins and contexts of the development of the Medienphilosophie. The following two parts are concerned with the identity of media philosophy – its metatheoretical characteristics contained in the writings of two prominent figures – Frank Hartmann and Sybille Krämer. The last part is devoted to the specificity of the scientific and philosophical discipline after the so-called media turn.